Enhancing Power Efficiency in FIR Filter VLSI Architecture for Seismic Signal Processing with Clock Gating - K. Rushendrababu; S. Siddaiah; V. Sai Siva Durga; P. Susmitha; Y. Vamsidhar Rao (International Journal of Scientific Research in Science and Technology, 2025)
For real-time seismic signal processing in a seismic alert system, finite impulse response (FIR) filters must exhibit low complexity, high processing speed, and adaptability. A widely used approach to reducing hardware complexity in digital FIR filters involves minimizing logic operators (LOs) and logic depths (LDs) through common sub-expression elimination (CSE). This paper presents a novel matrix-grouped CSE (MCSE) technique that outperforms conventional CSE methods by significantly reducing LOs and LDs. Additionally, a half-unit biased (HUB) rounding method is incorporated to mitigate truncation errors while maintaining design simplicity. To further optimize performance, the cut-set retiming technique is employed to minimize the critical-path delay (CPD). Two hardware-efficient FIR filter architectures—Design I and Design II—are introduced, integrating the proposed canonical signed digit (CSD)-based MCSE algorithm, HUB rounding, and cut-set retiming. Notably, Design II demonstrates a hardware-efficient implementation of a reconfigurable FIR filter. The architectures are implemented on both FPGA and ASIC platforms for hardware validation.
Keywords: Finite impulse response (FIR); half-unit biased (HUB); canonical signed digit (CSD); common sub-expression elimination (CSE); seismic signal